Elastic Scattering of Medium-Mass Heavy-Ions and the Compressibility of the Nuclear Equation of State - Koulouris, Stergios; Souliotis, Georgios A.; Pakou, Athina; Cappuzzello, Francesco; Carbone, Diana; Cavallaro, Manuela; Fasoula, Olga; Sgouros, Onoufrios; Soukeras, Vasileios; Veselsky, Martin (HNPS Advances in Nuclear Physics, 2026)
Preliminary results on the elastic scattering channel of the 70Zn (15 MeV/nucleon) + 64Ni reaction, studied with the MAGNEX large-acceptance spectrometer at INFN-LNS, are presented. This work is part of an extended effort to investigate reaction mechanisms in the Fermi energy regime, following previous analyses of momentum-per-nucleon distributions, angular distributions, and production cross sections of multinucleon transfer channels. Attention is here focused on elastic scattering of medium mass heavy ions and its sensitivity to the parameters of the nuclear equation of state (EOS). Experimental angular distributions were compared with Constrained Molecular Dynamics (CoMD) model calculations performed under different assumptions of nuclear matter compressibility (K = 200, 254, 308 MeV). The results indicate sensitivity of the elastic scattering differential cross sections to the compressibility of the nuclear EOS. Optical model calculations are also planned to complement the microscopic approach and provide complementary insight in the EOS.